Determinants of corporate disclosure on intellectual capital in Malaysian IPO prospectuses - Too, Shaw Warn; Somasundaram, Nakha Ratnam (Inder Science, 2011)
This research examines the determinants of intellectual capital (IC) disclosure in company initial public offerings (IPO) prospectus in the Malaysian context. An examination of the influence of the firm’s, management’s and the IPO advisors’ attributes (i.e., 11 independent variables altogether), on the extent of IC disclosure, was carried out. The data was collected through a content analysis of the IPO prospectus of 330 companies which were undergoing listing exercise in the Malaysian Securities from 2002–2008, by adopting the IC disclosure checklist used by Bukh et al. (2005), which is comprised of 78 items. The research shows that the extent of IC disclosure has increased significantly from 2002 to 2008. Another seven determinants that have been identified as significantly influencing the extent of IC disclosure are the company size, level of technology, foreign activity and performance, pre-IPO managerial ownership, reputation status of the managing underwriter and the reporting accountant.